Monocyte / high-density lipoprotein ratio and neutrophil-to-lymphocyte ratio in age-related macular degeneration (Annals of Medical Research, 2021)
None
Keywords: Age-related macular degeneration; monocyte-to-high-density lipoprotein ratio; neutrophil-to-lymphocyte ratio; systemic inflammation; neovascular AMD.